Socio-economic Analysis and Farming Practices in Coastal Cage Aquaculture in India - GEORGE, SAJU; Imelda-Joseph; Shoji Joseph; Anuraj, A; Santosh,B; Sekar,M; Shilta,M.T; Joe,K.; Kizhakudan; Tamilmani,G.; Kalidas,C.; Ambarish P. Gop; et al. (Journal of Indian Fisheries Association, 2024)
This study examines the socioeconomic characteristics, operational dynamics, and farming practices of mariculture cage farmers. The results indicate that cage farming is predominantly male-dominated (75.9%), and  most farmers (53.3%) where in the age group of  35–50 years. In terms of their occupational characteristics, 49.9% of farmers are primarily fishers whereas  31.1% consider cage farming as their main livelihood source, and 56.1% have adopted it as a secondary income source. Cage farming is capital-intensive, leading 23.6% of farmers to form some kind of  partnership to share the initial capital expenditure. It was also found that a significant 83 % of farmers are interested in joining a fish farmer producer organisation if given an opportunity.  Institutional support, mainly from ICAR-CMFRI (75.0%), has significantly influenced adoption. Most cage farmers ( 93.9%) have attended some type of  training in cage farming. Key factors influencing adoption of cage farming were institutional support (84.4%), economic potential (65.6%), and peer influence (35.4%). Farmers are using different dimension of cages wherein  rectangular (4x4x3 m3) and circular (6m diameter) cages were popular.  Popular species for cage farming were found to be asian sea bass (Lates calcarifer)  (90.6%), pearl spot (Etroplus suratensis)  (34.9%), and cobia (Rachicentron canadum)  (25.0%). Integrated Multitrophic Aquaculture (IMTA) is practiced by 13.2% of farmers. Harvesting practice followed is mostly  periodic (51.9%). While 63.7% have maintained same number of cage numbers, 24.1% of farmers have expanded their operations. Findings highlight the role of institutional support, financial considerations, and species selection in shaping cage farming. Strengthened policies and cooperative initiatives can enhance sectoral growth and sustainability. The study found that cage culture farmers were getting a BCR ratio of 2.11 in composite cage culture with seabass and Pearl sport in 4x4x3 m3 cage size indicating good financial viability.